Efficacy and safety of biphasic insulin aspart and biphasic insulin lispro mix in patients with type 2 diabetes: A review of the literature - Ajay Kumar (Indian Journal of Endocrinology and Metabolism, 2016)
Type 2 diabetes (T2D) represents an escalating burden worldwide, particularly in China and India. Compared with Caucasians, Asian people with diabetes have lower body mass index, increased visceral adiposity, and postprandial glucose (PPG)/insulin resistance. Since postprandial hyperglycemia contributes significantly to total glycemic burden and is associated with heightened cardiovascular risk, targeting PPG early in T2D is paramount. Premixed insulin regimens are widely used in Asia due to their convenience and effectiveness. Data from randomized controlled trials and observational studies comparing efficacy and safety of biphasic insulin aspart 30 (BIAsp 30) with biphasic insulin lispro mix (LM 25/50) and versus other insulin therapies or oral antidiabetic drugs (OADs) in T2D demonstrated that BIAsp 30 and LM 25/50 were associated with similar or greater improvements in glycemic control versus comparator regimens, such as basal–bolus insulin, in insulin-naÏve, and prior insulin users. Studies directly comparing BIAsp 30 and LM 25 provided conflicting glycemic control results. Safety data generally showed increased hypoglycemia and weight gain with premixed insulins versus basal–bolus insulin or OADs. However, large observational trials documented improvements in glycated hemoglobin, PPG, and hypoglycemia with BIAsp 30 in multi-ethnic patient populations. In summary, this literature review demonstrates that premixed insulin regimens are an appropriate and effective treatment choice in T2D.